جدليّة أسلمة الأدب العربي: الإشكاليّة والمفهوم (The controversy of Islamization of the Arabic literature: Problems and concept) - (Nasr el-DIn Ibrahim Ahmad), نصر الدين إبراهيم (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2014)
ملخص البحث: أفرزت فترة الحداثة وما بعده ان بعض الآراء الفلسفية والنظريات، والأيدلوجيّات المختلفة التي تأثر بها المجتمع العالمي، وأفضى إلى آثار سلبية، قادت في خاتمة المطاف إلى جمود عاطفة الإنسان، وتسلط الآراء الفكرية المنطقية الفلسفية التي أفرزت ما يُسمى بالمذاهب الغربية، وكل هذه المذاهب وما فيها من محتويات ومضامين قد أثّرت في أدبنا المعاصر تأثيرا سلبيا. ومما يؤسف له أن التقليد الأعمى لهذه المذاهب، هو ما دأب عليه كثير من أدبائنا المعاصرين، مما شوّه مفهوم الأدب، من أجل هذا، دعا بعض الأدباء الحادبين على مفهوم الالتزام في الأدب، ودوره في إصلاح الكون والإنسان والحياة إلى ما يسمى "بأسلمة الأدب"، فصارت هناك جدليّة بين الفريقين في الآراء والمنظور والمفهوم الحقيقي للأدب. الكلمات المفتاحية: الإسلامية- أولاد حارتنا- آيات شيطانية- نائب عزرائيل- الأدب الإسلامي. Abstract: The post-modern era had witnessed the emergence of different philosophical views, theories and ideologies that influence the masses. Consequently, this had resulted in some negative tendencies such as the dullness of emotion and the domination of philosophical logic in thoughts that gave rise to the Western doctrines. The contents of this philosophy had further influenced our modern literature in a negative manner. It is unfortunate that blind following of these doctrines was a found in many of our modern writers that distorted the meaning of literature. In response to this, some modern writers had made the call for the concept of ‘commitment’ in literature and what it promotes in terms of the restoration of the role of the universe, the man and the life that gave rise to the concept of Islamic literature. As a result of this, the concept of literature had been contested by both parties as to what it really stand for. Keywords: Islamization – ‘Aulad haratina’ – Satanic verses – The Deputy of Izrael – Islamic Literature. Abstrak: Zaman moden banyak menghasilkan falsafah, teori dan ideologi yang berbeza yang mana ia memberi kesan yang negatif kepada masyarakat dan akhirnya membawa manusia kepada pemikiran yang jumud hingga terbentuklah falsafah pemikiran yang berasaskan logik akal yang dinamakan pada hari ini sebagai pemikiran barat. Teori dan falsafah yang dibawa oleh barat ini telah memberi kesan yang negatif kepada kesusasteraan Arab moden. Bahkan yang lebih menyedihkan adalah ramai dikalangan sasterawan pada hari ini mengambil dan mengikut falsafah barat secara membuta tuli hingga merosakkan konotasi sastera itu sendiri. Oleh yang demikian itu, ada dikalangan sasterawan menyeru supaya berpegang kepada konsep sastera yang betul dan peranannya dalam memperbaiki kehidupan manusia iaitu apa yang dinamakan sebagai “islamisasi sastera”. Maka timbullah perdebatan diantara dua pihak tentang pendapat dan pandangan terhadap konsep sebenar sastera. Kata kunci: Islamisasi – Budak Jalanan – Ayat-Ayat Syaitan – Pembantu I’zrail - Sastera Islam.